Peningkatan Hasil Belajar Kognitif Peserta Didik pada Pembelajaran IPAS dengan Media Flashcard di Kelas VA SDN 2 Setu Wetan - Yustiani, Kharisma Fitria; Wahyuningsih, Asih; Fauziyah, Nita (ARZUSIN, 2025)
This research is motivated by a gap between learning objectives and student learning outcomes based on initial assessment results of IPAS learning in class VB at SDN 2 Setu Wetan, which is caused by the misalignment of teaching methods with students' learning styles. The purpose of this study is to describe the application of flashcard media in IPAS learning through a differentiated learning approach and to improve students' cognitive learning outcomes on the topic of "My Wealthy Indonesia." The research method used is classroom action research (CAR) based on the Kemmis & McTaggart model, which consists of two cycles. The subjects of the study are 35 students in class VB. Data were collected through observation sheets, interviews, documentation, and tests. Data analysis techniques were conducted quantitatively on test results and qualitatively on observation and interview data. The results of the study indicate that the application of flashcard media in differentiated learning can enhance student engagement and cognitive learning outcomes. The percentage of learning completeness increased from 77.14% at the beginning of cycle I to 94.29% at the end of cycle II. In addition, student involvement in group activities also increased, especially among students who were previously passive.